A TRANSDIAGNOSTIC PERSPECTIVE ON MENTAL DISORDERS (Годишен зборник на Филозофски факултет - Скопје, 2022)
The paper presents the current status of the transdiagnostic approach to psychopathology, an alternative model of describing and understanding mental health impairments, which attempts to bridge the gap between clinical reality and the diagnostic paradigm. By abandoning the boundaries (i.e. limitations) of diagnostic categories, this perspective provides opportunities for a more accurate conceptualization of processes underlying a wide range of disorders, either as risk factors for their occurrence or mechanisms that maintain them, as well as for proposing psychological interventions whose effectiveness transcends individual diagnostic entities. Following a brief overview of the weaknesses of categorical nosological systems, the dimensional representation of psychopathology is presented as a foundation for this perspective. Next, various approaches to defining and examining transdiagnostic processes are further presented, and empirical evidence on several extensively researched vulnerability factors is discussed. Finally, the specifics of transdiagnostic psychological interventions are briefly elaborated on, and, in conclusion, the current challenges and potential future directions of this paradigm are presented.